Investigating the Dynamics of Land Cover Change on Land Surface Temperature in Indian Himalayan Region: A Case Study of Srinagar, India (1991–2024) - Yadav A.; Chettry V.; Maurya A. (My University, 2025)
Indian Himalayan Region (IHR) has experienced substantial growth in anthropogenic activities combined with haphazard urban growth. Such changes have led to the degradation of the environmental quality and have placed human settlements at risk. Therefore, this study attempts to investigate the dynamics of land cover change on Land Surface Temperature (LST) for the Indian Himalayan city of Srinagar using multi-temporal Landsat satellite data from 1991 to 2024. Land cover maps (agriculture, built-up, vegetation, waterbodies, and fallow land), biophysical indices, and Landscape metrics were extracted to capture the dynamics of land cover change on LST. The results indicated that the built-up has expanded from 20.3% to 49.4%, while the extent of dense vegetation and waterbodies have declined from 23.5% to 8% and 9.3% to 6.3%, respectively, during the study period. Biophysical indices and LST correlation revealed a negative relationship between NDVI and NDWI with LST exhibited, i.e., vegetation and waterbodies coverage are associated with lower surface temperatures. The NDBI and LST represented a substantial positive linear correlation, i.e., built-up areas exhibit higher surface temperatures. The mean LST of the study area has risen by 6.31 ℃ during the study period, indicating the prevalence of the Urban Heat Island (UHI) effect. The landscape metrics revealed that the scattered built-up patches had expanded irregularly with increased built-up areas. The results from this study will assist policymakers in ensuring sustainable urban development in the city of Srinagar. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.